PELATIHAN MANAJEMEN USAHA BAGI PELAKU USAHA MIKRO KOTA BATAM - Heryenzus Heryenzus; Robert Situmorang; Jackhon Pahala Simanjuntak; Yopi Yopi (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2025)
Batam City as a free trade area has great economic potential for micro business actors, but limited managerial capabilities are often the main obstacle in business development. This Community Service (PkM) activity aims to increase business governance capacity for micro business actors in Batam City through systematic and applicable management training. The main problems identified include the lack of separation of personal and business finances, inefficient operational management, and suboptimal digital marketing strategies. The method of implementing activities is carried out through the preparation stage in the form of needs analysis, the implementation stage through interactive workshops and digital bookkeeping simulations, and the evaluation stage using pre-test and post-test instruments. The results of the activity showed a significant increase in managerial understanding of participants, which was marked by an average increase in evaluation scores of 50%. Participants are now able to prepare simple financial statements independently and implement production efficiency strategies. The conclusion of this activity is that increasing managerial literacy through a practical approach has proven to be effective in strengthening the business foundations of micro business actors, so that they have better competitiveness and higher business sustainability potential in a competitive market environment.